Assessing the resistance and bioremediation ability of selected bacterial and protozoan species to heavy metals in metal-rich industrial wastewater - Kamika, Ilunga (BioMed Central, 2013)
BACKGROUND: Heavy-metals exert considerable stress on the environment worldwide. This study assessed the resistance to and bioremediation of heavy-metals by selected protozoan and bacterial species in highly polluted industrial-wastewater. Specific variables (i.e. chemical oxygen demand, pH, dissolved oxygen) and the growth/die-off-rates of test organisms were measured using standard methods. Heavy-metal removals were determined in biomass and supernatant by the Inductively Couple Plasma Optical Emission Spectrometer. A parallel experiment was performed with dead microbial cells to assess the biosorption ability of test isolates. RESULTS: The results revealed that the industrial-wastewater samples were highly polluted with heavy-metal concentrations exceeding by far the maximum limits (in mg/l) of 0.05-Co, 0.2-Ni, 0.1-Mn, 0.1-V, 0.01-Pb, 0.01-Cu, 0.1-Zn and 0.005-Cd, prescribed by the UN-FAO. Industrial-wastewater had no major effects on Pseudomonas putida, Bacillus licheniformis and Peranema sp. (growth rates up to 1.81, 1.45 and 1.43 d(-1), respectively) compared to other test isolates. This was also revealed with significant COD increases (p < 0.05) in culture media inoculated with living bacterial isolates (over 100%) compared to protozoan isolates (up to 24% increase). Living Pseudomonas putida demonstrated the highest removal rates of heavy metals (Co-71%, Ni-51%, Mn-45%, V-83%, Pb-96%, Ti-100% and Cu-49%) followed by Bacillus licheniformis (Al-23% and Zn-53%) and Peranema sp. (Cd-42%). None of the dead cells were able to remove more than 25% of the heavy metals. Bacterial isolates contained the genes copC, chrB, cnrA3 and nccA encoding the resistance to Cu, Cr, Co-Ni and Cd-Ni-Co, respectively. Protozoan isolates contained only the genes encoding Cu and Cr resistance (copC and chrB genes). Peranema sp. was the only protozoan isolate which had an additional resistant gene cnrA3 encoding Co-Ni resistance. CONCLUSION: Significant differences (p < 0.05) observed between dead and living microbial cells for metal-removal and the presence of certain metal-resistant genes indicated that the selected microbial isolates used both passive (biosorptive) and active (bioaccumulation) mechanisms to remove heavy metals from industrial wastewater. This study advocates the use of Peranema sp. as a potential candidate for the bioremediation of heavy-metals in wastewater treatment, in addition to Pseudomonas putida and Bacillus licheniformis.